Rungkad Hakekat Penuntutan dalam penjelasan Pasal 132 Undang-Undang nomor 1 tahun 2023 tentang Kitab Undang-Undang Hukum Pidana (KUHP BARU) dan Kegalauan Penyidik/ Penyidik Pembantu Polri - marasin, ferlyanto; Koto, Zulkarnein (Jurnal Ilmu Kepolisian, 2024)
This is different from the term Wetboek van Strafprocesrecht, which in Indonesian means "Criminal Procedure Code". According to legal expert from Hasanuddin University Makassar; Hamzah (1985:13) the Dutch Minister of Justice emphasized that the term "Strafvordering" covers all criminal prosecution procedures. Therefore, it can be concluded that the Criminal Procedure Code in Indonesia is not a descendant of Dutch blue blood/a colonial product, while also confirming that the current Criminal Procedure Code does not merely discuss prosecution procedures. The explanation of Article 132 of the Law of the Republic of Indonesia Number 1 of 2023 concerning the Criminal Code reads "in this provision what is meant by "prosecution" is the judicial process which begins with an investigation". The explanation of Article 132 of the new Criminal Code is a butterfly effect phenomenon if not receiving special attention will certainly damage the essence of prosecutorial authority which is neatly structured in the Indonesian criminal procedural justice system. The explanation of Article 132 of the new Criminal Code does not at all understand Stufenbau's legal theory where the expanded role of prosecutors is in direct contrast to Article 30 paragraph (4) of the Law. -The 1945 Constitution which is the ground norm or basic norm. Apart from that, the Explanation of Article 132 of the New Criminal Code is too vulgar to rebel against the principle of Functional Differentiation which is already compatible with the Indonesian criminal procedural justice system. It requires awareness of all Polri personnel through education about the latent dangers of the explanation of Article 132 of the New Criminal Code. This is in order to explain that this article slightly confuses the existence of investigators/assistant investigators of the National Police so that investigative authority should not be compromised.